Interpreting Anselm's thought about divine justice: dealing with loose ends - Vreeswijk, Bernard J. D. van (Scottish journal of theology, 2016)
Over the last fifty years studies of Anselm of Canterbury's concept of divine justice have delivered different results. The aim of this article is to present the results of a new comprehensive inquiry, based on the interpretation of key passages about justice in Anselm's theological works. The article argues that Anselm works with three definitions of God's justice. The first is the most traditional: God's justice is his right dealing with good and bad. The second definition follows the Anselmian concept of God: God's justice is his acting according to his being that than which nothing greater can be conceived. The third definition is God's rightness of will, preserved for its own sake. The article concludes that the attempt to show how these three definitions are related to each other brings to light tensions and loose ends in Anselm's works.